2013
DOI: 10.1039/c3cp51259b
|View full text |Cite
|
Sign up to set email alerts
|

The structural and electronic properties of tubular gold clusters with a spinal support

Abstract: Scalar relativistic density functional theory (DFT) is used to investigate the structural and electronic properties of an endohedrally doped hollow tube of gold with a hexagonal cross-section, X(M)Au(N) (X = Si, Al and Au, M = 3, 6, 9 and N = 24, 42, 60). Only Si as a dopant can be encapsulated to provide a stable backbone to the parent tubular Au(N) whereas structures containing an Al or Au backbone are distorted into non-cage like structures as the size increases. The dopant atoms increase the electron densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Accordingly, Si doping in gold clusters is most widely studied using theoretical methodologies. Manzoor et al recently studied the effect of doping with Si on the reactivity of Au 7 0 cluster. They found that the presence of a Si atom within a Au cluster not only enhances the O 2 activation on Au 7 0 but also significantly reduces the activation barrier toward the formation of CO 2 from CO and O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Si doping in gold clusters is most widely studied using theoretical methodologies. Manzoor et al recently studied the effect of doping with Si on the reactivity of Au 7 0 cluster. They found that the presence of a Si atom within a Au cluster not only enhances the O 2 activation on Au 7 0 but also significantly reduces the activation barrier toward the formation of CO 2 from CO and O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The surge of interest in hollow nanostructures, together with the wide range of possibilities offered by nanoalloys with respect to elemental clusters, 17 has led recently to the study of bimetallic cages. [18][19][20][21] However, these studies are often limited to the investigation of a single metal atom encapsulated into a golden cage, [22][23][24][25][26][27] whereas a systematic study of the stability of golden cages after doping with other metallic species is still missing.…”
Section: Introductionmentioning
confidence: 99%